Cognitive image, affective image, cultural dimensions, and conative image: A new conceptual framework - Yang, Shaohua; Isa, Salmi Mohd; Yao, Yiyue; Xia, Jinyuan; Liu, Danping (Frontiers in Psychology, 2022)
Destination image is essential to tourists' loyalty and has been discussed in length among researchers and marketers in the tourism industry for decades. Based on a literature review, the destination image model, including cognitive image, affective image, and conative image, has been firmly established as an acceptable means to gain an understanding of tourists' behavior toward revisiting and recommendations. The understanding of the moderating role of cultural constructs is still unclear, especially in cross-cultural travel behavior. Therefore, this conceptual paper proposes an integrated model of cognitive-affective-conative image that includes the constructs of individualism and uncertainty avoidance. Based on the underpinning theories and empirical studies, this paper proposes affective image potentially mediates the correlation between cognitive image and conative image. This model also incorporated individualism and uncertainty as potential moderating effects between affective image and conative image. By integrating individualism and uncertainty avoidance into the theoretical model from the perspective of tourism, this paper contributes to a more comprehensive understanding of the influence of travel behavior on emerging tourism marketing.